The Influence of Perceived Usefulness, Ease of Use, and Sharia Financial Literacy on QRIS Users: A Case Study of UINSU Student MSMEs - Temuju, Mas Imam; Imsar, Imsar; Rahmani, Nur Ahmadi Bi (SENTRALISASI, 2026)
The purpose of this study is to examine how MSME actors who are UINSU students use QRIS in relation to perceived utility, perceived ease of use, and Islamic financial knowledge. 26,512 current students from the 2022 cohort make up the research population, and 100 responders were chosen proportionately from each faculty. The approach used is quantitative with SEM-PLS to test causal relationships between variables. The study's findings indicate that while Islamic financial literacy has no discernible impact on QRIS adoption, perceived utility and simplicity of use do. Perceived usefulness is the most dominant factor because students feel the efficiency of transactions, ease of record-keeping, and increased business professionalism. Perceived ease of use also plays an important role in reducing technological barriers. On the contrary, Islamic financial literacy has not yet become a determinant of usage. The implication is that the adoption of QRIS needs to be focused on strengthening benefits and convenience as well as more practical and contextual Islamic financial learning.